Functional Outcomes after Salvage Transoral Laser Microsurgery for Laryngeal Squamous Cell Carcinoma. (October 2016) - Fink, Daniel S.; Sibley, Haley; Kunduk, Melda; Schexnaildre, Mell; Sutton, Collin; Kakade-Pawar, Anagha; McWhorter, Andrew J.
Objectives: Transoral laser microsurgery (TLM) has been increasingly used in lieu of total laryngectomy to treat malignancy after definitive radiation. There are few data in the literature regarding functional outcomes. We retrospectively reviewed voice and swallowing outcomes in patients who underwent TLM for recurrent laryngeal carcinoma. Study Design: Case series with chart review. Setting: Tertiary care center. Subjects and Methods: Forty-two patients were identified with recurrent squamous cell carcinoma of the larynx after definitive radiation therapy from 2001 to 2013: 28 patients with glottic recurrence and 14 with supraglottic recurrence. Swallowing outcomes were evaluated by gastrostomy tube dependence, the MD Anderson Dysphagia Inventory, and the Functional Oral Intake Scale. Voice outcomes were evaluated by the Voice Handicap Index and observer-rated perceptual analysis. Results: No significant difference was noted between mean pre- and postoperative MD Anderson Dysphagia Inventory scores: 78.25 and 74.9, respectively ( P = .118, t = 1.6955). Mean Functional Oral Intake Scale scores after TLM for supraglottic and glottic recurrences were 6.4 and 6.6, respectively. Of 42 patients, 17 (40.5%) required a gastrostomy tube either during radiation or in conjunction with the salvage procedure. Of 17 patients, 15 resumed sufficient oral diet for tube removal. Patients' mean Voice Handicap Index score did increase from 34.3 to 51.5 ( P = .047), and their mean perceptual score did decrease from 60.0 to 45.3 ( P = .005). However, at 1-year follow-up, there was no significant difference in perceptual score: 61.1 to 57.1 ( P = .722). Conclusions: TLM is a successful surgical option for recurrent laryngeal cancer with acceptable functional outcomes.